The Effect of Honey on Bacterial Growth, Protein Degradation, Amino Acids Contents, and Volatile Compounds of Milks at Storage - Khusniati, Tatik; Widyastuti, Yantyati (BRIN, 2005)
Pasteurized milks spoiled at refrigerated storage due to growth of psychrotrophic bacteria. Honey which contain antibacterial and aromatic compounds may be used as supplement to inhibit psychrotrophic bacterial activities. To know nutritional and flavor compounds of milks with and without honey, effect of honey on bacterial growth protein degradation, amino acids, and volatile compounds of stored milk were detected. Bacterial growth, protein degradation, amino acids, and favor compounds were detected by total plate counts. formol titration, HPLC, and GCMS, respectively. The results how that bacterial growth and protein degradations in honey milks were lower than that without honey. Bacterial growth (5.2x103 -9.3x106 cfu/mL) and protein degradation (2.37-2.59%) in honey whole milks were lower than that (6.2x104-6.5x107 cfu/mL) (2.54-2.88%) in skim milks, respectively P<0.05). At 10 days after use by date, changing between amino acids contents in whole milks with and without honey were more significant than that or skim milk (P<0.05); and volatile compounds percentages in honey whole milks were higher than that without honey. While that in honey skim milks vice versa. Honey caused decreasing bacterial growth and protein degradation, changing amloo a id 'contents and producing volatile compounds of stored milk, and honey whole milk were better than honey skim milks.